Knowledge And Awareness Regarding the Provision of First Aid Among Adults in Victims of Maxillofacial Trauma in Urban Population-Dubai. (Journal of Pharmaceutical Negative Results, 2022)
Background: Maxillofacial trauma refers to any injury to the face or jaw caused by physical force, foreign objects, or burns. Certain special precautions must be observed if you are giving first aid to a person who has suffered a maxillofacial injury. Maxillofacial trauma includes injury to soft tissues and bone fractures. Such injuries require immediate first-aid treatment such as the establishment of a free airway, control of haemorrhage and treatment of shock. Support of the facial structures and positioning of the patients face downwards are also essential life-saving measures.Aim : To assess the Knowledge and awareness regarding the provision of first aid among adults in victims with maxillofacial trauma in urban population.Objective :Most adults are unaware about the first aid provided for the victims with maxillofacial trauma in urban population, therefore this survey is done to assess the knowledge held by adults and then help raise awareness among them.Methodology: This was a survey based study, done using an online forum, SurveyPlanet. The survey was circulated amongst a population in Dubai and 83 responses were collected. From the obtained responses, the results were tallied and evaluated. Results: From the survey conducted it was noticed that most people are unaware about the provision of first aid by bystanders for Maxillofacial trauma victims.Conclusions: Only 31.3% of the population who answered the questionnaire were aware of the first aid methods that were provided for victims with Maxillofacial trauma. To increase awareness, campaigns and pamphlets may be circulated to help make the common urban population aware and proficient